EXPLAINING TOURIST SATISFACTION WITH COMMUNITY-BASED TOURISM IN THE MEKONG DELTA REGION, VIETNAM - Quoc Nghi NGUYEN; Van Nam MAI; Thi Hong Loc HOANG (Geo Journal of Tourism and Geosites)
In the Mekong Delta region (Vietnam), community-based tourism is developing and achieving impressive results. To maintain this success, community tourism sites should pay special attention to improving tourist satisfaction. Therefore, this study aims to demonstrate the factors influencing tourist satisfaction with community-based tourism in the Mekong Delta region (Vietnam). A mixed research method was used, combining qualitative and quantitative research to test the research hypotheses. The research data were collected using a convenient sampling with a sample size of 350 tourists who had experienced community-based tourism services in the Mekong Delta region. The research results have pointed out 08 factors that positively affect tourist satisfaction with community-based tourism in the Mekong Delta region, including trust, responsiveness, assurance, empathy, tangible facilities, perceived price, cultural interaction, and local cuisine. Among these, the trust factor has the most powerful impact on tourist satisfaction. Several management implications have been proposed for community tourism sites to enhance service quality and tourist satisfaction with community-based tourism in the Mekong Delta region, Vietnam.